Remarks for the Plenary Session of the Summit of Heads of State of the Central American Integration System - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
Robert B. Zoellick, President of the World Bank Group, noted that the region could be more competitive if, working together, you removed bottlenecks to growth; modernized customs systems; facilitated trade; improved infrastructure, integrated your energy grid, and enhanced transport; strengthened the education and skills of your people; and created a better environment for private investment, small business and entrepreneurs. He spoke on the following topics: past and recent integration achievements; an agenda for integration; and the package of World Bank Group initiatives. He announced a two-year trade facilitation window, support for an INCAE training program for public administration, a technical assistance facility to support trade promotion, and a program to support judicial transparency.